Valorization of polyphenolic compounds from food industry by-products for application in polysaccharide-based nanoparticles - Rosales, Thiécla Katiane Osvaldt; Fabi, João Paulo (Frontiers in Nutrition, 2023)
In the last decades, evidence has indicated the beneficial properties of dietary polyphenols to human health. In vitro and in vivo studies support that the regular intake of these compounds may be a strategy to reduce the risks of some chronic non-communicable diseases. Despite their beneficial properties in human health, they are poorly bioavailable compounds. Thus, the main objective of this review is to explore how nanotechnology improves human health while reducing environmental impacts with the sustainable use of vegetable residues, from extraction to the development of functional foods and supplements. This extensive literature review discusses different studies based on the application of nanotechnology to stabilize polyphenolic compounds and maintain their physical-chemical stability. Food industries commonly generate a significant amount of solid waste. Exploring the bioactive compounds of solid waste has been considered a sustainable strategy in line with emerging global sustainability needs. Nanotechnology can be an efficient tool to overcome the challenge of molecular instability, especially using polysaccharides such as pectin as assembling material. Complex polysaccharides are biomaterials that can be extracted from citrus and apple peels (from the juice industries) and constitute promising wall material stabilizing chemically sensitive compounds. Pectin is an excellent biomaterial to form nanostructures, as it has low toxicity, is biocompatible, and is resistant to human enzymes. The potential extraction of polyphenols and polysaccharides from residues and their inclusion in food supplements may be a possible application to reduce environmental impacts and constitutes an approach for effectively including bioactive compounds in the human diet. Extracting polyphenolics from industrial waste and using nanotechnology may be feasible to add value to food by-products, reduce impacts on nature and preserve the properties of these compounds.